Preliminary Characterization of MEDLE-2, a Protein Potentially Involved in the Invasion of Cryptosporidium parvum - Li, Baoling; Wu, Haizhen; Li, Na; Su, Jiayuan; Jia, Ruilian; Jiang, Jianlin; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2017)
Cryptosporidium spp. are important causes of diarrhea in humans, ruminants, and other mammals. Comparative genomic analysis indicated that genetically related and host-adapted Cryptosporidium species have different numbers of subtelomeric genes encoding the Cryptosporidium-specific MEDLE family of secreted proteins, which could contribute to differences in host specificity. In this study, a Cryptosporidium parvum-specific member of the protein family MEDLE-2 encoded by cgd5_4590 was cloned and expressed in E. coli. Immunofluorescent staining with antibodies generated from the recombinant protein showed the expression of the protein in sporozoites and development stages. In vitro neutralization assay with the antibodies partially blocked the invasion of sporozoites. These results support the potential involvement of MEDLE-2 in the invasion of host cells.